Migration, Remittances and Human Capital Investment in Kenya - Annie Laurie Hines; Nicole B. Simpson (Institute of Labor Economics (IZA), 2018)
This paper investigates the relationship between international migration, remittances and human capital investment in Kenya. We use household level data from the 2009 Kenya Migration Household Survey (produced by the Africa Migration Project) to test our hypothesis and uncover a positive and significant relationship between the amount of international remittances a household receives and the amount of expenditures allocated to education (for all levels of education). We consider various robustness checks and find that our results hold up to various specifications, including an instrumental variable approach.
Keywords: F24; I25; J61; O12; 330; migration; remittances; human capital